Understanding the Role of Think-Pair-Share Strategy in Mathematics Classroom - Ramadhani, Amalia; Karida , Mujadilah Putri; Wahyunengsih, Wahyunengsih (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Low student engagement in mathematics learning remains a serious challenge in various schools and universities in Banten Province. Although the Think-Pair-Share (TPS) strategy is recognised as effective in promoting active participation and conceptual understanding, its implementation in the field is uneven and lacks contextual evidence. This study aims to analyse the perceptions of mathematics teachers and lecturers regarding the implementation of TPS, specifically in terms of anticipated benefits, obstacles experienced, and opportunities for classroom implementation. Using a quantitative descriptive approach, data were collected through a survey of 26 respondents who offered to participate in the study. The instrument was a closed questionnaire with five Likert scales with 45 statement points covering nine indicators of TPS implementation. Data were analysed using descriptive statistics, which involved calculating the average score for each indicator and creating a frequency distribution. The results showed that respondents generally had a positive perception of TPS, particularly in fair students’ understanding of mathematical concepts and communication skills. However, the main obstacles involved limited implementation time and diversity in student participation. Some respondents also mentioned the lack of practical training and the difficulty in adapting strategies to the characteristics of the class. Although the sample size is limited, this study makes an initial contribution to understanding the dynamics of TPS implementation in the local context. It is recommended that teacher training focus on the technical aspects of TPS implementation and be accompanied by flexible and context-based guidance to support the effectiveness of cooperative learning in mathematics classes.